Design eø [videorecording] : the economies of being environmentally conscious - Fettig, Tad; Westrate, Elizabeth; Anisko, Eva; Kontentreal (Firm); PBS Home Video ([Alexandria, Va.] : Distributed by PBS Home Video)
The first season of this series examines the economies of being environmentally conscious in green building design. The first program, The green apple, uses New York City, particularly One Bryant Park and the Solaire, to demonstrates how the ubiquitous skyscraper can be a model of environmental responsibility. The second episode, Green for all, features architect and activist Sergio Palleroni as he works to provide design solutions to regions suffering from social and humanitarian crises. Shows projects in East Austin, Tex. and with the Yaqui Indians in Mexico where architecture students are helping residents build low-cost, environmentally-friendly homes using local materials. The third program, The green machine, follows Mayor Richard M. Daley as he strives to make Chicago "the greenest city in America" with numerous LEED (Leadership in Energy and Environmental Design)- certified buildings, a solar-powered public transportation system, and many green roofs, including one on Chicago's City Hall. The fourth episode, Gray to green, takes the notion of the three R's (reduce, reuse, recycle) to grand proportions by turning Boston's "Big Dig" steel and concrete waste into spectacular residential design. The fifth program, China : from red to green? depicts a rapidly urbanizing country at its tipping point and finds a sustainable solution in Steven Holl's Beijing project, which will have the largest geothermal heating/cooling and greywater recycling system in the world upon completion. The sixth program, Deeper shades of green, presents three visionaries who are changing the face of architecture and environmentalism and features some of their projects. Focuses on Ken Yeang and his "bio-climatic" National Library of Singapore, Werner Sobek and R128, his energy- efficient, steel and glass box house, and William McDonough and his model sustainable village of Huangbaiyu, China